Possibilities of Physical Medicine in the Treatment of Median Nerve Paralysis – Case Report - Jarosław Pasek; Grzegorz Cieślar; Tomasz Pasek (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Post-traumatic lesions of peripheral nerves prove to be extremely difficult in treatment and planning rehabilitation. Most frequently, those lesions have been caused by accidents or other circumstances. The lesion severity degree and consequences may be very substantially. This execution usually operating intervention with following rehabilitation. The recent years this is the dynamic development of method from physical medicine which more and more often help led treatment. Case Report. The case study presents the result of treatment with use of spatial magnetic field in two patients (51 year-old and 31 year-old) after trauma injury-induced injury of the upper extremity with subsequent paralysis of median nerve. Discussion. In the course of therapy, provided in outpatient clinic, the patients underwent a 45-day cycle of procedures with the use of generator for spatial magnetic field therapy. Before admission to the Clinic, the patient had undergone outpatient treatment, without satisfactory results. The therapy applied using spatial magnetic field, created optimum conditions for regeneration and reinnervation of damaged nerves, leading to improved functional condition of treated patients. Conclusions. In the treatment of trauma injury of peripheral nerve important is introduction the proper treatment and the rehabilitation. Utilization of new apparatus, also the apparatus to spatial magnetic fields can in future support treatment and also accelerate their return to health. (JNNN 2015;4(3):117–120)